Tobacco Use Surveillance among School Personnel of Madhyamik Vidyalays of Pimpri-Chinchwad, Pune, Maharashtra, India: A Serial Cross-sectional Study - Sahana Hegde Shetiya; S. L. Jadhav; Rakesh Gupta (Journal of Indian Association of Public Health Dentistry)
Introduction: School teachers are role models for the children. Hence, this questionnaire study was undertaken with the objective of assessing tobacco usage, knowledge and attitude, school policy and curriculum among school personnel of 19 Madhyamik Vidyalaya’s in Pimpri Chinchwad Municipal Corporation, Pune District before and after implementation of the Tobacco Free School program “tobacco control program: Save our future generation.” Materials and Methods: A total of 160 teaching and nonteaching staff in 2021 at baseline and 153 in 2023 at follow-up were selected through probability proportional to size sampling. As part of the questionnaire development, face and content validity were carried out by subject matter experts, followed by translation, test–retest reliability, setting up a code book, and pre and pilot testing. Chi-square test was applied to determine the strength of association between the pre- and postsurvey data. Results: 1%–2% used smokeless tobacco and supari, with the teachers having due concern for the youth about tobacco use. Twelve to 25% (pre- and postsurvey) were aware that tobacco products can be bought within 100 yards of the school premises. Sixty-eight to 83% (pre- and postsurvey) (P < 0.001) agreed on having nonclassroom programs and 87%–95% being aware of school policy preventing tobacco use among students (P < 0.05). Discussion: Use of Smokeless Tobacco (SLT) with or without sweetened supari is more prevalent than smoking among the staff, though social desirability bias may be present. More than half of the educators were not aware or thought that SLT is as harmful as smoking and less than one quarter of the staff received training for tobacco prevention. However, 87-88% (post-survey) students and staff followed existing school policy. Staff were aware that one of the tobacco control measure is increasing the price of tobacco products. Conclusion: Although the school authorities are trying to enforce a tobacco ban, conduct regular checks on school bags, and if needed, discuss the same with parents, the teachers in the school need to be educated on tobacco control issues and help with cessation.